Chemical and metallurgical thermodynamics - Prasad, Krishna Kant. (New Age International, 2007)
This book, Chemical and Metallurgical Thermodynamics, is based on author?s deep study of the subject as well as his long teaching experience. The emphasis has been on clarity of concepts, in addition to practical applications of thermodynamics in metallurgical process.